READINESS OF VERTICAL AGENCIES OF THE DIRECTORATE GENERAL OF TREASURY AS FINANCIAL ADVISOR - Marwanto Harjowiryono; Rudy Widodo; Aditya Agung Satrio; Teguh Dwi Prasetyo (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study investigates the readiness of the Directorate General of Treasury (DJPb) to assume its emerging role as a financial advisor to local governments—an area that remains underexplored in the literature on organizational change within fiscal institutions. The research addresses a gap by examining how internal factors such as organizational support, commitment to change, and technical capability influence individual readiness, and whether advocacy by change agents moderates these relationships. A quantitative approach was employed using a survey distributed to DJPb personnel in Regional Offices and State Treasury Service Offices (KPPN), analyzed through structural equation modelling (SEM) with SmartPLS. The findings reveal that commitment to change and technical capability significantly enhance readiness, while organizational support shows limited influence except in Sumatra. The moderating role of change agents was not supported. These results suggest that strengthening commitment and technical skills is crucial for enabling DJPb’s advisory function, with implications for adaptive communication strategies in public sector reform.